Manfaat Matrikektomi Kimia Dalam Mencegah Rekurensi Onychocryptosis - Gusti Ngurah Pradnya Wisnu (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2020)
Introduction: Onychocryptosis is a nail disease characterized by pain, redness, swelling or pus formation due to growing nail digging into the paronychium. Onychocryptosis is often encountered in daily practice and a general practitioner must be able to perform nail avulsion as one of the treatment option. Nail avulsion is an effective treatment for onychocryptosis but this prochedure does not prevent recurrence. For this purpose, a matricectomy can be performed following a nail avulsion procedure. This prochedure, although effective, is not widely discussed. Discussion: Matricectomy works by destroying the nail matrix so that the nail does not grow cutting the paronychium. Several studies showed the superiority of nail avulsion followed by chemical matricectomy in preventing recurrence of onychocryptosis compared to nail avulsion procedures alone. Matricectomy can be carried out using chemical agents such as phenol, TCA or sodium hydroxide. These three agents will cause necrosis of nail matrix in the area where they are applied. Saveral studies showed that the use of these chemical agents in matricectomy has a high success rate in preventing recurrence of onychocryptosis. Conclusion: Matricectomy can be done following nail avulsion to prevent reccurence of onychocryptosis. It can be carried out using phenol, TCA or sodium hydroxide. These three agents have comparable effectiveness. Keywords: Matricectomy, Nail avulsion, Onychocryptosis